PERSONALIZED E-LEARNING SYSTEMS: A USER MODELING TECHNIQUE (Pakistan Journal of Science, 2016)
For providing the personalization feature to e-learning systems, a Human Computer Interaction HCI technique, User Modeling was considered in system design. This study was undertaken to propose a technique to model the students’ learning styles for personalized e-learning system. Bayesian Network BNwas used to model the students’ learning styles and Kolb’s learning styles theory was used to know the students’ learning styles and preferences. The objective of the study was to propose a user modeling technique for personalized e-learning systems to understand the elearners’ requirements and needs to enhance their learning.Using BN, Conditional Probability Tables CPTs were determined for all four learning styles provided by Kolb’s theory. The threshold values were used to determine the learning styles of students during an online course. We found that BN technique determined successful as from the Divergers 100%., 75% Assimilator, 50% Accommodators and 75% Convergers were identified accurately.
Keywords: Personalized e-learning systems; User Modeling; Bayesian Network; Learning Styles